The chloroplast genome of an important herb species, Ephedra sinica (Ephedraceae). Issue 2 (3rd July 2019) - Lin, Yifeng; Cao, Tianyi; Zhang, Quan
Abstract: Ephedra sinica has been utilized by humans for over 5000 years as Chinese herbal medicine in China. In this study, we reported the complete chloroplast genome of E. sinica . The chloroplast genome of E. sinica is 109, 550 bp in length as the circular, which harbors a large single-copy (LSC) region of 59, 962 bp, a small single-copy (SSC) region of 8106 bp and separated by a pair of inverted-repeat (IR) regions of 20, 742 bp each. The overall nucleotide content of the chloroplast genome: A of 31.2%, T of 32.1%, C of 18.4% G of 18.3%, and 36.7% GC content. This chloroplast genome contains 118 genes, which includes 74 protein-coding genes (PCGs), 36 transfer RNA (tRNAs) and 8 ribosome RNA (rRNAs). Phylogenetic analysis result showed that E. sinica was most closely related to Ephedra equisetina in the family Ephedraceae using the Neighbor-Joining (NJ) method.